2015
DOI: 10.1017/s0007114515002482
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of calcium and magnesium and the metabolic syndrome in the National Health and Nutrition Examination (NHANES) 2001–2010 data

Abstract: Higher dietary intakes of Mg and Ca, individually, have been associated with a decreased risk for the metabolic syndrome (MetSyn). Experimental studies suggest that a higher intra-cellular ratio of Ca:Mg, which may be induced by a diet high in Ca and low in Mg, may lead to hypertension and insulin resistance. However, no previous epidemiological studies have examined the effects of the combined intake of Mg and Ca on MetSyn. Thus, we evaluated the association between dietary intakes of Ca and Mg (using 24-h re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
3
34
1
3
Order By: Relevance
“…Choi et al [28] detected hair Ca concentrations in 456 subjects from Korea and found that the hair Ca concentrations were significantly lower in the MetS group than in the control group (non-MetS vs. MetS: 9.366 ± 4.567 vs. 9.259 ± 0.350 mg/dl, p = 0.046). Other literature found similar correlation between Ca intake and MetS [60,62] . A large crosssectional study involving 10,066 adult women found an inverse association between the highest quintile (>1,004 mg/day) and the lowest quintile (<562 mg/day) of Ca intake and MetS [62] .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Choi et al [28] detected hair Ca concentrations in 456 subjects from Korea and found that the hair Ca concentrations were significantly lower in the MetS group than in the control group (non-MetS vs. MetS: 9.366 ± 4.567 vs. 9.259 ± 0.350 mg/dl, p = 0.046). Other literature found similar correlation between Ca intake and MetS [60,62] . A large crosssectional study involving 10,066 adult women found an inverse association between the highest quintile (>1,004 mg/day) and the lowest quintile (<562 mg/day) of Ca intake and MetS [62] .…”
Section: Discussionsupporting
confidence: 74%
“…The relationships between Ca and MetS found in previous epidemiologic studies have yielded different results [23,28,[60][61][62] . The inverse relationship between MetS and Ca concentrations in the present study was also observed in several previous studies [28,61] .…”
Section: Discussionmentioning
confidence: 86%
“…Much of the evidence indicates that the anti-carcinogenic potential of Ca relies on its interrelation and correlation with vitamin D. However, experimental evidence suggests that an increased level of Ca alone is sufficient to trigger apoptosis (10) . Increased risk of breast cancer has been linked with several chronic diseases such as diabetes, obesity and the metabolic syndrome (38)(39)(40)(41) , all of which have been suggested to be inversely associated with Ca intake (42)(43)(44) . Therefore, Ca intake may indirectly be associated with lower breast cancer risk through its association with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Дієта повинна бути ба-гатою на вітаміни A, C, E, Р, РР, В 2 , В 6 , які чинять гіполіпидемічну, депресорну дію, покращують нир-ковий і коронарний кровообіг, зменшують проник-ність судинної стінки. Слід обмежувати введення вітамінів групи D, які сприяють розвитку атеро-склерозу, і груп нутрієнтів, що мають коагулюючі властивості (містяться у вершках, сметані, верш-ковому маслі), продуктів, багатих на біогенні аміни (сир, оселедець, боби, ананаси, помідори), які збу-джують нервову систему й підсилюють діяльність ОГЛЯД / REVIEW серця (бульйони, підливи, шоколад, гострі закуски, приправи, копченості) [6,13,33,39].…”
Section: лікувально-превентивне харчування при гіпертонічній хворобіunclassified